PVP-assisted MOF-derived Fe3O4/C powders for microwave absorption applications - V. Kavoosi; S.M. Masoudpanah (Heliyon)
Metal-organic framework (MOF) derived porous Fe3O4/C powders were applied for absorption of microwaves in the frequency range of 1–18 GHz. The effects of the polyvinylpyrrolidone (PVP) additive on the synthesis of MIL101-(Fe) precursor were studied by various characterization methods. By adding PVP, the impure hematite phase (α-Fe2O3) with magnetite phase (Fe3O4) was disappeared and the particular morphology was transformed to the porous rod-like, leading to the increase of specific surface area from 150 to 282 m2/g. Furthermore, the saturation magnetization (Ms) of Fe3O4/C powders reached a maximum value of 47 emu/g at a proper amount of PVP. A thin absorber (2.6 mm) made of 50 wt% Fe3O4/C powders and 50 wt % paraffine absorbed the whole of X frequency band (8–12 GHz) with a minimum reflection loss of −20 dB at a matching frequency of 10 GHz. Adjusting the permittivity and permeability parameters of the Fe3O4/C powders via adding PVP was responsible for their better microwave absorption performance.